Evaluating Housing Policy in Egypt During President Sisi’s Term - Jumaah, Aya Sadeq; Abduallah, Khairullah Sabhan (Journal of Posthumanism, 2025)
The study addressed the housing crisis in Egypt, focusing on the efforts made by successive governments, especially during the era of President Abdel Fattah El-Sisi since he assumed power in June 2014. During this period, Egypt witnessed an unprecedented urban renaissance in the field of housing, as housing policy became one of the priorities of the Egyptian government within Egypt’s Vision 2030. The efforts are attributed to confronting the increasing population growth, which is expected to reach 150 million people by 2050. The study addressed the challenges associated with population growth and its impact on limited resources, in addition to the decline in tourism economy revenues since 2011. The study also examined the need for a partnership between the state, the private sector and the local community to transform housing plans into tangible results that meet the needs of low-income people. It also discussed the importance of housing as a basic human right and its role in achieving social security and stability. The hypothesis was based on the fact that rapid population growth constitutes a major obstacle to government efforts to solve the housing crisis, especially with the limited available resources.